Data processing system of continuous temperature measurement for liquid steel - Xianzhang Feng; Junwei Cheng; Zheng Wang; Yanmei Cui; Yongqiang Wei; Junxing Hou; Zhiqiang Jiang (Functional Materials, 2017)
Six different methods of accurate measurement of the temperature of liquid steel in real time are analyzed. Using a comparison and analysis, a fast and accurate mathematical model is obtained. Проведен анализ шести различных методов точного измерения температуры жидкой стали в реальном времени. С помощью сравнения и анализа результатов получена быстрая и точная математическая модель. Проведено аналіз шести різних методів точного вимірювання температури рідкої сталі в реальному часі. . За допомогою порівняння і аналізу результатів отримана швидка і точна математична модель.